Configuring the Asian Infrastructure Investment Bank : power, interests and status - Chen, Ian Tsung-yen (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Studying the Asian Infrastructure Investment Bank (AIIB) through the lens of international relations (IR) theory, Chen argues that it is inappropriate to treat the AIIB as either a revisionist or a complementary institution. Instead, the bank is still evolving and the interaction of power, interests, and status that will determine whether the bank will go wild. Theoretically, the current shape of the AIIB will influence global strategic conditions and global perceptions of the bank itself, consequently affecting China's level of dissatisfaction with its power and status in the international financial system and maneuvering in the AIIB. To empirically show that, this book presents the evolution of the AIIB, compares the bank with its main competitors in the Asia-Pacific region, and conducts ten comparative case studies to show how countries around the world have positioned themselves in response to the emergence of the AIIB"--
An integrative framework : power, interests, status and global responses -- China and the evolution of the AIIB -- AIIB in comparative perspectives -- Asia-Pacific participation in the AIIB -- European participation in the AIIB -- Countries shunning the AIIB -- Conclusion: Crouching tiger, hidden dragon.
OCLC-licensed vendor bibliographic record.
Keywords: Asian Infrastructure Investment Bank; Development banks -- Asia; Banks and banking, International -- Asia; China -- Foreign economic relations; POLITICAL SCIENCE / General; POLITICAL SCIENCE / International Relations / Trade & Tariffs